Household symptomatic contact screening of sputum smear positive tuberculosis patients at the DOTS clinic of SGT hospital, Gurugram - Naresh, Siddharth; Sharma, Monika; singh, Varinder; Anand, Bhupinder Kaur; Verma , Pankaj; Marwaha, Manvinder Pal Singh (Indian Journal of Community Health, 2022)
Background: Contact screening was conducted under ICMR (REFERENCE ID: 2019-07811) programme in villages near SGT hospital, Gurugram. Objective: To evaluate risk factors, extent of spread of tuberculosis among household contacts of tuberculosis cases and to create awareness. Methods and Material: Address of TB cases were taken from RNTCP register at DOTS clinic, SGT medical college. Then all household contacts of positive cases were screened, counselled and advised to approach ASHA Workers if such symptoms appear. Data was analysed using appropriate statistical methods. Results:21 Index cases along with 94 household contacts were screened. 61.90% families still use chullahs for cooking. 76.1% families have overcrowding. 3) 61.90% families had inadequate ventilation 4) 19.05%families were aware about the spread of this disease. 5)Only 23.80% families practised adequate sanitation methods and precautions6) 42.8% Index cases had a history of smoking. 7) 44.4% 4 continue to smoke with infection. The association of adequate sanitation with presence of awareness was found to be statistically significant. (p-value<0.05). Other factors were not significantly associated with level of awareness regarding prevention of tuberculosis spread among study participants. Conclusions: Contact screening is an effective tool and it gives the real-time picture of TB in India.